2007
DOI: 10.1080/00207540600786715
|View full text |Cite
|
Sign up to set email alerts
|

Using dispatching rules for job shop scheduling with due date-based objectives

Abstract: terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae and drug doses should be independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…This block is inspired by the remarks of Dominic et al (2004) who concluded that 9 The results of the comparative study are displayed in Table 2 for each of the five objective functions. It is worth noting the similar comparative studies has been made by other authors, such as Waikar et al (1995), Holthaus and Rajendran (1997), Rajendran and Holthaus (1999), Holthaus and Rajendran (2000), Jayamohan and Rajendran (2000), Jayamohan and Rajendran (2004), Dominic et al (2004) and Chiang and Fu (2007), but with a slightly different focus or limited scope compared to our full comparison on the five objective functions. The results can be briefly summarized per objective function along the following paragraphs.…”
Section: Comparative Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This block is inspired by the remarks of Dominic et al (2004) who concluded that 9 The results of the comparative study are displayed in Table 2 for each of the five objective functions. It is worth noting the similar comparative studies has been made by other authors, such as Waikar et al (1995), Holthaus and Rajendran (1997), Rajendran and Holthaus (1999), Holthaus and Rajendran (2000), Jayamohan and Rajendran (2000), Jayamohan and Rajendran (2004), Dominic et al (2004) and Chiang and Fu (2007), but with a slightly different focus or limited scope compared to our full comparison on the five objective functions. The results can be briefly summarized per objective function along the following paragraphs.…”
Section: Comparative Resultsmentioning
confidence: 83%
“…Section A.2 list the single priority rules together with their mathematical formulation. For this overview, we based ourselves on the papers of, among others, Panwalkar and Iskander (1977), Blackstone et al (1982), Baker (1984), Russell et al (1987), Vepsalainen and Morton (1987), Anderson and Nyirenda (1990), Waikar et al (1995), Holthaus and Rajendran (1997), Rajendran and Holthaus (1999), Jayamohan and Rajendran (2000), Holthaus and Rajendran (2000), Dominic et al (2004), Mizrak and Bayhan (2006) and Chiang and Fu (2007). Finally, in Section A.3, more information is given on the combination of the single rules.…”
Section: Appendix Amentioning
confidence: 99%
“…The method schedules jobs on particular machines (groups of machines) based on certain priority rules, according to which subsequent operations are chosen. There are several advantages of the method: quick solution, analysis of alternative scheduling scenarios or easy implementation of the method [22,23].…”
Section: Job Scheduling Methodsmentioning
confidence: 99%
“…There are several other rules, such as SRPT, LTWK and SPT/TWK, commented by Chiang and Fu (2006). Extensions of SPT incorporate, under combined conditions, other goals, also with good efficiency and late operations.…”
Section: The Priority Dispatching Rulesmentioning
confidence: 99%